PENGARUH PROMOSI DAN MUTASI PEGAWAI TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MODERATING: (Studi Kasus Pada Kejaksaan Negeri Yogyakarta) - Wicaksana, Joan Kurniawan; Nurwahyudi, Muhammad Robi (UNIKA Santo Thomas, 2025)
This study aims to determine the extent to which promotion and transfer affect employee performance with motivation as a moderating variable at the Kejaksaan Negeri Yogyakarta. The sampling technique used is accidental sampling, with a total of 50 respondents from the office. Data collection was conducted using questionnaires, interviews, and observations. The data analysis tool used is SEM-PLS with SmartPLS 4.1 software. The conclusions of this study are: (1) Promotion has a negative and insignificant effect on employee performance. (2) Transfer has a negative and insignificant effect on employee performance. (3) Motivation has a positive and significant effect on employee performance. (4) Promotion has a negative and insignificant effect on employee performance with motivation as a moderating variable. (5) Transfer has a negative and insignificant effect on employee performance with motivation as a moderating variable.